SP0109 How To Perform Clinical History and Physical Examination?. (15th July 2016) - Doherty, M.
Abstract : The GALS (gait, arms, legs, spine) screen is useful to detect musculoskeletal (MSK) abnormality as part of a general assessment (1). However, for a person with MSK complaints a more detailed assessment is required to determine the diagnosis and impact on the patient. A thorough history alone usually suggests the single most likely cause for the patient's problem(s). The examination that follows should be a targeted assessment in which the practitioner selects the required skills from a range of competencies according to specific elements in the history (i.e. not a uniform set of identical procedures in each patient). The overall assessment needs to be holistic and individualised as the enquiry proceeds, since the impact of any condition is person specific and influenced by many factors (e.g. psychosocial factors, illness perceptions, sleep, comorbidity etc.). This presentation will cover key principles and considerations related both to the history and examination (2). Examples include: (1) in the history: determination of pain localisation and features that associate with radiated pain; important pain and stiffness characteristics that differentiate mechanical usage-related pain, inflammatory pain, acute crystal synovitis pain, destructive bone pain and neurogenic pain; non-specific symptoms of inflammation (2) in the examination: usual order of inspection at rest, inspection during movement, then palpation at rest and during movement; contrasting clinical findings that differentiate joint and peri-articular problems; detection of "stress pain" (pain worse in tight-pack positions but reduced/absent in loose-pack positions - the most sensitive sign of inflammation); examination for effusion, soft-tissue and firm swelling; use of resisted active movements and stress tests for peri-articular lesions. With experience, following a thorough history and examination the combined aspects of the history and examination which differentiate between major categories of MSK conditions permit pattern recognition and a confident clinical diagnosis in the majority of cases. A simple way of assembling the clinical findings to enable them increasingly to point to a likely single diagnosis will be presented. EULAR learning resources available at http://www.eular.org/edu_training_dvd.cfm include: (1) The "GALS" screen and (2) Principles of the musculoskeletal history and examination. Disclosure of Interest: None declared